1988
DOI: 10.1002/jor.1100060415
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of fretting corrosion of orthopaedic materials

Abstract: Two models were used to study fretting corrosion of surgical alloys. In the first, the amount of load and motion between plates and screws was controlled, and corrosion rates of stainless steel and MP35N were determined by measurements of component weight loss and metal ion concentration in the test solutions. Stainless steel had the higher rate of fretting corrosion. The addition of 10% serum to saline resulted in a significant reduction of the corrosion rate of stainless steel and MP35N. The use of stainless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Considering the high nickel content of the alloy, there are, understandably, concerns that nickel may dissolve from the material due to corrosion and cause adverse effects. On the other hand, other alloys that contain high levels of nickel, such as MP35 N (a Co alloy with 35 weight percent Ni), or 300 series stainless steel (approximately 10 weight percent Ni) exhibit good biocompatibility, and have long been used as implants in orthodontics, orthopedics, and cardiovascular applications [11]. Several studies have measured nickel release during the exposure of Nitinol implants to body fluids.…”
Section: Biocompatibility and Corrosionmentioning
confidence: 98%
“…Considering the high nickel content of the alloy, there are, understandably, concerns that nickel may dissolve from the material due to corrosion and cause adverse effects. On the other hand, other alloys that contain high levels of nickel, such as MP35 N (a Co alloy with 35 weight percent Ni), or 300 series stainless steel (approximately 10 weight percent Ni) exhibit good biocompatibility, and have long been used as implants in orthodontics, orthopedics, and cardiovascular applications [11]. Several studies have measured nickel release during the exposure of Nitinol implants to body fluids.…”
Section: Biocompatibility and Corrosionmentioning
confidence: 98%
“…Previous studies have investigated electrochemical behavior after oxide fracture. [3][4][5][6][7][8][9] Some of these studies have shown that sample potential, solution chemistry, and proteins 10 effect the repassivation process. However, none have attempted to characterize the mechanical properties of the oxide or its mechanical behavior during oxide fracture.…”
Section: Introductionmentioning
confidence: 98%
“…Metal tongues and splinters were also seen associated with screw threads and in the periphery of plate screw holes. Jorgensen and Gjerdet [2] in their study of SS and titanium miniplates and screws concluded that Defects of mechanical nature were found in all SS [8].…”
Section: Discussionmentioning
confidence: 99%